2022
DOI: 10.52945/rac.v35i2.1354
|View full text |Cite
|
Sign up to set email alerts
|

Tolerância de genótipos de arroz irrigado (Oryza sativa) ao estresse por calor na antese

Abstract: O objetivo deste trabalho foi avaliar o efeito do estresse térmico (calor) na antese sobre o desempenho agronômico de genótipos brasileiros modernos de arroz irrigado. As variedades SCS124 Sardo, SCS122 Miura, SCS121 CL, SCS116 Satoru, SCSBRS Tio Taka, Epagri 109 e as linhagens SC 491 ME, SC 676, SC 792, SC 806, SC 817, SC 849 foram avaliadas. Na antese, as plantas correspondentes ao tratamento de estresse por calor foram transferidas para uma câmara de crescimento por quatro dias sob temperaturas de 38ºC (dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…At the same time (2015 -2020), experiments were carried out at the EEI in partnership with the Agroveterinary Center of the State University of Santa Catarina -Udesc/CAV, in a controlled growth chamber (Instalafrio; software Sitrad). These studies confirmed the resilience of SC 806 not only to low temperatures (15-17 ºC) but also to high temperatures (up to 38 ºC), which can be summarized by a lower sterility percentage when compared to other cultivars (Stürmer et al 2019, Souza et al 2022). However, SCSBRS126 Dueto only has intermediate cold tolerance in germination and vegetative stage.…”
Section: Pedigree and Breeding Methodssupporting
confidence: 70%
See 1 more Smart Citation
“…At the same time (2015 -2020), experiments were carried out at the EEI in partnership with the Agroveterinary Center of the State University of Santa Catarina -Udesc/CAV, in a controlled growth chamber (Instalafrio; software Sitrad). These studies confirmed the resilience of SC 806 not only to low temperatures (15-17 ºC) but also to high temperatures (up to 38 ºC), which can be summarized by a lower sterility percentage when compared to other cultivars (Stürmer et al 2019, Souza et al 2022). However, SCSBRS126 Dueto only has intermediate cold tolerance in germination and vegetative stage.…”
Section: Pedigree and Breeding Methodssupporting
confidence: 70%
“…Added to all this, the main trait to stress out is that SCSBRS126 Dueto has the ability to tolerate cold and heat during the reproductive stage for some days, which is demonstrated by lower sterility rates compared with control cultivars (daily temperatures of 15-17 °C and night ones of 10-12 °C or daily of ≥38 °C, during 3-4 days). This was proved under controlled stress trials and also validated by two natural field cold cases (Stürmer et al 2019, Souza et al 2022, Marschalek et al 2023).…”
Section: Traits Performancementioning
confidence: 70%
“…37 In turn, the most sensitive phase is the reproductive phase, when apical stem bud differentiation occurs at the beginning of the ear, because heat stress in this phase reduces the number of fertile flowers per spikelet and the number of grains per ear. 38 There is little scientific information that characterizes the tropical region for wheat production in Brazil, [39][40][41] especially in the southeastern region. The greatest challenge is to produce in a profitable and stable manner regarding the productivity and quality of rainfed wheat within the Brazilian tropical wheat crop region, where most environmental conditions are considerably different from subtropical conditions, mainly due to the greater probability of experiencing drought and stress during the crop cycle.…”
Section: Resultsmentioning
confidence: 99%
“…Outra particularidade da SC 806, descoberta durante trabalhos colaborativos entre UDESC e Epagri (tese de doutorado), foi sua tolerância a altas temperaturas (SOUZA et al 2022). Isso pode indicar a existência de mecanismos sobrepostos de tolerância no período reprodutivo, o que já foi reportado por XIONG (2013).…”
unclassified